Differential Expression of Brain Cannabinoid Receptors between Repeatedly Stressed Males and Females may Play a Role in Age and Gender-Related Difference in Traumatic Brain Injury: Implications from Animal Studies - Xing, Guoqiang; Carlton, Janis; Jiang, Xiaolong; Wen, Jillian; Jia, Min; Li, He (Frontiers in Neurology, 2014)
Inconsistent gender differences in the outcome of TBI have been reported. The mechanism is unknown. In a recent male animal study, repeated stress followed by TBI had synergistic effects on brain gene expression and caused greater behavioral deficits. Because females are more likely to develop anxiety after stress and because anxiety is mediated by cannabinoid receptors (CB1 and CB2), there is a need to compare CB1 and CB2 expression in stressed males and females. CB1 and CB2 mRNA expression was determined in the amygdala, hippocampus, prefrontal cortex and hypothalamus of adolescent male and female rats after 3 days of repeated tail-shock stress using qPCR. Prefrontal cortex CB1 and CB2 protein levels were determined using Western blot techniques. Both gender and stress had significant effects on brain CB1 mRNA expression levels. Overall, females showed significantly higher CB1 and CB2 mRNA levels in all brain regions than males (p<0.01). Repeated stress reduced CB1 mRNA levels in the amygdala, hippocampus and prefrontal cortex (p<0.01, each). A gender x stress interaction was found in CB1 mRNA level in the hippocampus (P<0.05), hypothalamus (p<0.01) and prefrontal cortex (p<0.01). Within sex one-way ANOVA analysis showed decreased CB1 mRNA in the hippocampus, hypothalamus and prefrontal cortex of stressed females (p<0.01, each) but increased CB1 mRNA levels in the hypothalamus of stressed males (p<01). There was a gender and stress interaction in prefrontal CB1 receptor protein levels (p<0.05) which were decreased in stressed females only (p<0.05). Prefrontal CB2 protein levels were decreased in both male and female animals after repeated stress (P<0.05, each). Conclusion: High basal levels of cannabinoid receptor expression in young naïve females could protect against TBI damage whereas stress-induced cannabinoid receptor deficits could predict a poor outcome of TBI in repeatedly stressed females. Further animal studies could help evaluate this possibility.